A Formal Synthesis of Camptothecin via a Photocatalytic Decarboxylative Radical Addition. Issue 35 (24th July 2019) - Liu, Qian; Huang, Guanxin; Liu, Minjie; Chen, Fener
Abstract : A convergent fragment‐coupling strategy for the synthesis of camptothecin is described. The key step is a photocatalytic decarboxylative radical Michael addition that attaches the ABC rings to the E ring fragment, constructing the main structure of camptothecin in five steps. This work illustrates a new strategy for the synthesis of alkaloids of the camptothecin family. Abstract : A convergent fragment‐coupling strategy for the synthesis of camptothecin is described. The key step is a photocatalytic decarboxylative radical Michael addition that attaches the ABC rings to the E ring fragment.